2019
DOI: 10.1111/jvim.15416
|View full text |Cite
|
Sign up to set email alerts
|

Cardiorenal and endocrine effects of synthetic canine BNP1‐32 in dogs with compensated congestive heart failure caused by myxomatous mitral valve disease

Abstract: Background The effects of synthetic brain natriuretic peptide (BNP1‐32) on cardiorenal and renin angiotensin aldosterone system in dogs with naturally occurring congestive heart failure (CHF) are unknown. Objectives To evaluate the cardiorenal and endocrine effects of SC administered synthetic canine BNP1‐32, with or without furosemide, in dogs with CHF caused by myxomatous mitral valve disease (MMVD). Animals Seven client‐owned male dogs with compensated American College of Veterinary Internal Medicine stage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 48 publications
0
6
0
4
Order By: Relevance
“…Кардіологія це один із напрямків ветеринарної медицини, який найбільш інтенсивно розвивається. За останні роки було проведено кілька значних досліджень в області лікування серцевої недостатності, були введені нові методи діагностики, виявлено генетичні особливості окремих патологій та з'явилися нові лікарські засоби, наприклад: пімобендан, поліненасичені жирні кислоти, силденафіл, левосимендан, торасемід, небіволол, лізиноприл, клопідогрель та деякі інші (Zhulikova, 2016;Varkholiak, 2016;Tjostheim et al, 2019;Yata et al, 2019). Разом з тим, даних про застосування нових терапевтичних засобів за серцево-судинної патології недостатньо.…”
Section: вступunclassified
“…Кардіологія це один із напрямків ветеринарної медицини, який найбільш інтенсивно розвивається. За останні роки було проведено кілька значних досліджень в області лікування серцевої недостатності, були введені нові методи діагностики, виявлено генетичні особливості окремих патологій та з'явилися нові лікарські засоби, наприклад: пімобендан, поліненасичені жирні кислоти, силденафіл, левосимендан, торасемід, небіволол, лізиноприл, клопідогрель та деякі інші (Zhulikova, 2016;Varkholiak, 2016;Tjostheim et al, 2019;Yata et al, 2019). Разом з тим, даних про застосування нових терапевтичних засобів за серцево-судинної патології недостатньо.…”
Section: вступunclassified
“…Several peak bodies have produced guidelines on care of dogs and cats at different life stages, including the American Association of Feline Practitioners (AAFP) 1, 2 , the American Animal Hospital Association (AAHA) 3,4 , and the Australian Veterinary Association 5 . All of these recommend regular health checks (annual for adults, and every 6 months for seniors and older), with diagnostic testing included, especially as animals age.…”
Section: N13mentioning
confidence: 99%
“…In addition to examining existing treatment options for CHF, Mariko also studied the potential of the natriuretic peptide system as a therapeutic target in dogs with CHF. In a recently published article, 4 she identified that the cardiorenal effects of BNP1-32 (a type of natriuretic peptide) were diminished in dogs with CHF caused by myxomatous mitral valve disease. This suggested defects in what is essentially a protective mechanism in the context of CHF and is a finding that prompts further investigations into therapeutics targeting this system.…”
Section: A New Focus In Congestive Heart Failure?mentioning
confidence: 99%
“…According to the classification of Professor G. V. Domrachev, in domestic animals, cardiovascular pathology is divided into diseases of the myocardium, pericardium, endocardium and diseases of the blood vessels. There is a close relationship between the above pathologies, age and animal breeds (Undhad et al, 2012;Varkholiak, 2016;Zhulikova, 2016;Yata et al, 2019).…”
Section: Introductionmentioning
confidence: 99%